Workplace well-being from development of consciousness through purposeful leadership - Maheshwari, Anil K. (Journal of management, spirituality & religion, 2024)
This paper constructs a model for enhancing workplace well-being (WB) from development of consciousness (DC), through purpose driven leadership (PL). A morally higher and ethical organizational purpose can help facilitate the accomplishment of higher purposes of the individuals, leading to greater engagement, fulfilment, and well-being in the organization. This paper reviews 20 theories of leadership based on the inner domain of leaders, 10 scales of WB, and five perspectives on PL, and relates them all to DC. It also describes V-theory of transcendence to support DC through multiple practices and help the leadership in developing their higher purpose. The paper finally presents some propositions for future research on the model, and implications for practice.